2009
DOI: 10.5089/9781451871494.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent French Export Performance: Is there a Competitiveness Problem?

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the authors and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.Recently, the export performance of France relative to its own past and relative to a major trading partner, Germany, deteriorated. That deterioration seems related to the geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The business cycle literature suggests that the supply shocks are labour productivity‐driven. This corresponds with the evidence of Kabundi and Nadal De Simone (2009), who attribute the difference in competitiveness between France and Germany to the productivity of the latter country.…”
Section: Resultssupporting
confidence: 89%
“…The business cycle literature suggests that the supply shocks are labour productivity‐driven. This corresponds with the evidence of Kabundi and Nadal De Simone (2009), who attribute the difference in competitiveness between France and Germany to the productivity of the latter country.…”
Section: Resultssupporting
confidence: 89%
“…10 Similar models have recently been used by Giannone et al (2002), Forni et al (2009), Eickmeier (2007, and Kabundi and Nadal De Simone (2007). 11 In general factors are I(0), given that they are extracted from I(0) series (or series that have been made stationary).…”
Section: Common Versus Idiosyncratic Componentsmentioning
confidence: 91%
“…Thus, France's weaker performance should be sought especially at the export side, having been relatively unable to capitalize on the rise of EMEs. Indeed, Kabundi and Nadal De Simone ( 2009 ) have noted that French export performance in the 2000s lagged behind its own past record and compared with that of Germany over the same period. They concluded that '[t]raditional variables that explain international trade, such as the exchange rate, relative unit labor costs, and demand pressure seem insuffi cient to illuminate the recent decline in France's export performance' ( 2009 : 3) but that rather 'France's weaker export performance in the 2000s is refl ected both in terms of geographical destination and in terms of product composition ' ( 2009 : 13).…”
Section: Trade Structures Innovation Regimes and Non-price Competitimentioning
confidence: 99%